"Talk to me, not at me": obese women's experiences of birth and their encounter with birth attendants—a qualitative study. Issue 1 (1st January 2020) - Thorbjörnsdottir, Katrin Erna; Karlsen, Ida Emilie; Dahl, Bente; Røseth, Idun
ABSTRACT: Purpose : To explore the birth experiences of obese women in regard to their encounter with birth attendants. Methods : Qualitative, in-depth interviews with 10 women were conducted in February 2020. Data were analysed using a descriptive phenomenological method. Results : Four interrelated constituents were identified: The preconception and prejudice of being unhealthy and less able; Being unique among all the other unique women; "Talk to me, not at me"—the importance of information and communication, and; Feeling secure enough to be in the 'birthing bubble'. Conclusion : For the women in our study, being obese meant experiencing challenges as well as opportunities during childbirth and in their encounter with birth attendants. Experiences of preconceptions, alienation, a focus on risk and a loss of autonomy in encounters with birth attendants were found to negatively impact the birthing process. The women desired affirmative and inclusive encounters; these kinds of encounters may improve the birth experiences of obese women.